Eating Difficulty, Science and Parents’s Parenting. - meta rikandi; Novia Ulan Sari (JIK-JURNAL ILMU KESEHATAN, 2018)
Difficulty eating is symptom or sign of deviation or abnormality is happening to the child’s body. The preliminary survey of four foreig kindergartent in Padang obtained that foreigh kindergartent I has a higher difficulty eating. The aims of this reseach is to determine the correlation between knowledge and parent’s parenting with difficulty eating in preschool children in foreign kindergarten 1 Padang 2016.The type of this research is descriptive correlative with cross sectional approach. This research was conducted in foreign kindergarten 1 Padang from February to July 2016. The population of the research were 43 parents of preschoolers by using total sampling technique. The research used a questionnaire with quided interviews. Proceeded the data by using computerize system. The analysis of the data used is univariate and bivariate analysis.The results obtained (55.8%) of preschool children have difficulty eating, low knowledge 48.8%, 41.9% with poor parenting. chi square test concluded that there is a significant correlation between knowledge (p=0,000), and the parents’s parenting (p=0.000) with difficulty eating in preshool children in foreign kindergarten 1 Padang 2016.Provide information to parents that difficulty eating effect on children’s nutrition affect the development of children, and to teach parents how to modify the appearance of children eat more interested in eating.